Media-Tech Companies as Agents of Innovation: From Radical to Incremental Innovation in a Cluster - Ana Milojevic; Leif Ove Larsen (Media and Communication, 2024)
During recent decades new players, forms, and practices have been entering the journalism field, prompting a re-examination of journalism’s professional and organizational boundaries. Many scholars argue for expanding the scope of journalism studies beyond the newsrooms to encompass actors labelled as strangers, peripheral players, or interlopers. Those actors do not belong to traditional journalism but are becoming involved in the production of news, challenging journalism borders from the inside and out. Their influence has been growing and scholarship is increasingly mapping out these strangers and assessing their role in journalism innovation. In this article, we examine the role of one type of implicit interloper in journalism innovation: media-tech companies. We consider companies that provide video management and virtual reality services as implicit interlopers, due to their connection to journalism through the boundary object of news production and lack of claim over journalistic authority. We argue that media-tech companies have been under-researched based on a review of literature on innovation according to Holton and Belair-Gagnon’s (2018) typology of interlopers. Therefore, we examine what kind of innovation comes from the periphery of journalism, and the prerequisites for and the role of those innovations in the context of a specific cluster. We conducted a case study of Media City Bergen based on a thematic analysis of semi-structured elite interviews with executives of media-tech companies. Our findings show how media-tech companies bring innovation to production and distribution, content, and content consumption. Furthermore, they show how disruptiveness and the degree of innovations change with the maturation of the cluster.